2009
DOI: 10.1177/1043454209343209
|View full text |Cite
|
Sign up to set email alerts
|

Transitioning Survivors of Central Nervous System Tumors: Challenges for Patients, Families, and Health Care Providers

Abstract: Survivors of central nervous system tumors (SCNST) are a growing group of cancer survivors who require risk-based, long-term health care due to the chemotherapy, surgery, and radiation they have received.Although treatment strategies are being developed to reduce morbidity and mortality, ultimately this subgroup of pediatric cancer survivors often faces moderate to severe late effects of their treatment.As a result, they will need lifelong health care that includes risk-based health care due to cancer treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 114 publications
(140 reference statements)
0
7
0
Order By: Relevance
“…The developmental maturation of young adult childhood cancer survivors should be considered when introducing their transition to adult health care providers who will be assuming the responsibility for their care. However, many challenges exist in the successful transition of this population (Bashore, 2011; Eshelman-Kent, Gilger, & Gallagher, 2009). Young adult survivors may not disclose their disability.…”
Section: Background/significancementioning
confidence: 99%
See 1 more Smart Citation
“…The developmental maturation of young adult childhood cancer survivors should be considered when introducing their transition to adult health care providers who will be assuming the responsibility for their care. However, many challenges exist in the successful transition of this population (Bashore, 2011; Eshelman-Kent, Gilger, & Gallagher, 2009). Young adult survivors may not disclose their disability.…”
Section: Background/significancementioning
confidence: 99%
“…They may not be able to maintain compliance because of being used to pediatric providers (and parents) taking care of their needs. Survivors of central nervous system tumors have many challenges to independence including many physical and cognitive disabilities they acquire due to cancer treatment (Eshelman-Kent et al, 2009).…”
Section: Background/significancementioning
confidence: 99%
“…Study participants identified a treatment summary and access to the guidelines as essential tools in caring for survivors, however only 28% of providers had received this information (Suh et al, 2014). This poor communication can result in ASCC receiving inadequate follow-up (Eshelman-Kent et al, 2009).…”
mentioning
confidence: 98%
“…This same study found pediatric oncologists' comfort level with caring for survivors decreases as survivors age yet the healthcare providers still preferred to follow their patients for as long as possible . Transition of care is further complicated by the bond oncologists form with their patients or a belief that adult providers will not be able to provide an equal level of care (Eshelman-Kent, Gilger, & Gallagher, 2009). This creates a challenge for survivors who may find themselves caught between several providers, none of whom are able to provide the comprehensive care necessary for their complex medical needs.…”
mentioning
confidence: 98%
See 1 more Smart Citation